The Social and Political Meanings and Implications of The Muludan Tradition in Urban Communities - Masyhuri, Muhammad; Wildan, David (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This paper explores the Maulid Tradition within the socio-cultural context of urban society, focusing on the city of Semarang. The Maulid Tradition not only reflects religious spirituality but also has significant social and political implications. This research employs a field study method to analyze the Maulid celebrations across various mosque communities in Semarang. The findings indicate that these celebrations serve as a medium for strengthening community identity and social interaction, as well as creating a space for discussing relevant social issues. Furthermore, the Maulid Tradition plays a role in social mobilization and reinforces identity politics within a multicultural society. With the dynamics of tradition, transition, and innovation, communities are able to interpret the Maulid Tradition in a modern context, fostering collective awareness and cooperation, as well as promoting interfaith tolerance. The conclusion of this study emphasizes that, despite differing views on the Maulid celebrations, this tradition remains an important means to strengthen the identity and solidarity of the Muslim community in Semarang.